Turfloop testimony : the dilemma of a black university in South Africa - Nkondo, G. M. (Raven Press, 1976)
Refer to the book
Book
Keywords: Universities; Academic staff; Race relations; Black education; Black university; University of the North (South Africa); Race discrimination -- South Africa; Universities and colleges, Black; Bantu-speaking peoples, Education; Education, Higher; Universities and colleges -- South Africa; Universities and colleges -- Professional staff